Break time as the time to choose. For an educational planning after the coronavirus - Michele Corsi (Firenze University Press, 2020)
This paper is dedicated to the contemporary society and culture with a progressive perspective particularly focused on the families and the schools, in the light of the current coronavirus pandemic that has triggered new reflections and has proposed, or re-proposed, some important values. In reference to this lesson, the author writes about an educational planning that concerns these institutions. With a primary task entrusted to Italian pedagogy and training.   Tempo di pausa, tempo di scelta. Per una progettazione educativa dopo il coronavirus Il contributo indaga, ovviamente con uno sguardo in progress, la società e la cultura contemporanee sui versanti particolarmente delle famiglie e delle scuole, alla luce dell'attuale pandemia da coronavirus che ha attivato nuove riflessioni e proposto, o riproposto, taluni valori fondamentali. Nel solco di questa lezione, l'autore dà spazio a una progettazione educativa che riguarda questi istituti. Con un compito primario affidato alla pedagogia e alle didattiche italiane.